O devido processo legal coletivo de massa apesar da cultura jurídica do autointeresse - Silva, Bruna Bier da (2020)
The present work deals with the theme of collective protection of mass litigation. For that, the cultural individualism present in contemporary society is analyzed as an obstacle to the advances of procedural collectivism. Still, the text presents the historical context of the advent of collective protection of mass rights in the country, the influences of American law in this sense, as well as its main distinctions in relation to Brazilian collective procedural law. In addition, the advances incorporated into the Brazilian collective civil procedural system are referred to since the advent of the Public Civil Action Law, followed by the Consumer Protection Code and, later, the 2015 Civil Procedure Code. In this context, the author points out the need to conceive of mass rights as truly collective rights. Thus, she argues that the incorporation of tools for the collectivization of individual demands in the Brazilian legal system is a necessary measure. In the end, the author highlights the development need of the Brazilian system with regard to legitimacy, individual res judicata of the collective sentence, satisfaction of collective sentence and the structural decisions, in order to promote the greatest effectiveness regarding collective protection in Brazil.